The challenges of supply market scanning A comparative study of supply market scanning for mature- and innovative technology in the automotive industry - Rittsten, Johan; Land, Adam (My University, 2019)
The automotive industry is experiencing quick technological developments in areas such as automation, connectivity and electromobility. This pushes large automotive OEMs to innovate and at the same time provide their more mature technology to customers. This calls for scanning the market to fulfil two parallel needs; both to find technical innovation in the market and to find the best possible suppliers for mature segments. Literature on the area suggest that there might be different challenges associated with scanning for innovative technology compared to mature technology, but no studies have explicitly been done to compare the cases. This study therefore aim to investigate what the different challenges are in supply market scanning for mature technology, compared to the challenges associated with scanning for innovative technology. The study follows a qualitative approach and is based on data collected through 19 interviews. The interviews was divided into two categories, one targeting people in the organisation conducting supply market scanning for mature technology and one targeting people conducting it for more innovative technology. The study finds that the challenges of supply market scanning for mature technology have similarities to that of innovative technology, but that there are a few key differences. Supply market scanning for mature technology mostly faces challenges related to areas of information gathering, knowledge and experience, cross-functionality and network and storing and sharing information. Examples of challenges are: purchasers must have a big network, not having guidelines of how to do supply market scanning, making gathered information accessible to those of need it and not losing built up experience. Regarding supply market scanning for innovative technology they also face the challenge of making information accessible to those of need it, but more significantly they have different challenges related to the areas mindset, legal aspects and specifications. These areas include challenges about making the organisation open to scan for innovation despite the uncertainty it infer, adapting legal documents to fit new types of suppliers and being able to specify innovative technology. The study discusses possible ways to address the identified challenges in order for large automotive OEMs to improve their supply market scanning. The study does for example conclude that such companies should reduce job rotation, introduce formal guidelines for how to conduct supply market scanning, introduce a functional central database for supply market intelligence and change mindset in regards to innovative technology.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics